PENERAPAN ACTIVITY BASED COSTING PADA TARIF JASA RAWAT INAP DI RSUI BANYU BENING BOYOLALI TAHUN 2020 - Teguh Priyono; Alean Kistiani Hegy Suryana; Andria Referli (Universitas Boyolali, 2021)
The background of this research is that hospitals related to cost of goods are still struggling with the traditional cost system, the cost of the resulting product provides distorted production cost information, both under and over costing, thus affecting the determination of hospitalization rates. As an anticipation, it can be implemented to calculate the cost of products or services using Activity Based Costing (ABC). Research method: This research is a type of comparative research. The subjects in this study were RSUI Banyu Bening Boyolali, as for the object of research, namely the determination of inpatient room rates at the Banyu Bening Boyolali Hospital and the determination of inpatient room rates based on the ABC method. The data were obtained through interviews and based on the financial statements of the hospital. The data analysis technique is descriptive analysis technique through a comparative approach. The results of the study reflect that the calculation using the ABC method found 6 treatment classes experienced over cost and 1 treatment class experienced under cost. The underlying factor is the imposition of overhead costs on each product. In the traditional cost accounting method, the overhead costs for each product are concentrated in one of the cost drivers. This has an impact on the distortion of overhead costs. While the Activity Based Costing (ABC) method, overhead costs are charged to each cost driver. In the end, the Activity Based Costing (ABC) method is able to allocate the cost of activities in each treatment room accurately according to the consumption of each activity.